MULTI-BAND GRAPHIC EQUALISER BASED ON GYRATORS - SemenovА. О.; StalchenkoО. V.; KhlobaА. А.; Pinaiev, B. O.; Krystoforov, A. V. (Systems and Technologies, 2023)
Studies of the properties of human hearing have shown that the perception of loudness depends on both the frequency and intensity of sound. A person is able to compare the loudness of sounds of different frequencies. This allows us to construct so-called equal loudness curves (isophones). From them, it can be concluded that when the volume level is reduced, a person perceives sound components in the low and high frequencies of the sound range poorly, and at frequencies from 2 to 6 kHz, the ear is most sensitive to sounds. Therefore, it is with the help of an equalizer that sound correction is performed in accordance with equal volume curves. The purpose of this paper is to find a way to build an active eight-band equalizer to adjust the frequency response shape. This task can be solved in several ways. In the preliminary study, the three most common control principles were identified and analyzed, namely graphic equalizers based on an operational amplifier, bandpass filter signal addition, and an active filter with a feedback loop. Comparison of the latter with an equalizer based on an operational amplifier gave the following result: both have a uniform frequency response, but compared to the low-Q filters, the gyrator-based circuits have a higher quality, which gives an advantage to the operational amplifier-based equalizer because to obtain better quality factor and better stability of the EQ parameters based on the inclusion of a bandpass filter in the feedback loop, more complex filters that can accommodate two OPs and more elements must be used, which is not economical and will lead to an increase in size. It was also noticed that when adjusting the depth of control, the largest increase will be at the extreme positions of the slider, while at the middle positions, the slider has little effect on the depth, which is a big disadvantage. The same effect was observed for the developed scheme but with a smaller impact. But these effects are insignificant and can be ignored. The worst results are obtained with the equalizer with the addition of bandpass filter signals since it has frequency response fluctuations along the entire frequency axis at the middle positions of the sliders, and it also has the disadvantage of adjusting the frequency response in the attenuation direction, which is insignificant compared to the gain side. In order to increase the depth of control in the attenuation direction, it is necessary to increase the quality factor of the filters, and this, in turn, will lead to an increase in frequency response fluctuations, so it is undesirable to use this scheme.